Dynamic performance of the plasma‐triggered‐based protective gas switch used in the hybrid UHVDC system. Issue 4 (12th December 2022) - Wang, Wen; Gao, Keli; Li, Zhibing; Qu, Xuebin; Zhang, Ran; Wang, Yongxing
Abstract: Following the design demands of the protective switch used in ±800 kV hybrid UHVDC system, a plasma‐triggered‐based protective gas switch (PTGS) is developed by performing the comparative study of its dynamic performance by considering the arc dynamic behaviour induced by the transverse magnetic field (TMF)‐based electrode used in the PTGS. The PTGS‐based electrode, as the core component, is designed with a helical‐slotted structure, the TMF could drive the arc between moving from the electrode centre to the electrode edge and then rotate rapidly along the edge. A 3D magnetohydrodynamic model (MHD) was established to computationally evaluate the effects of electrode structure variation on arc rotation characteristics. The model was verified by comparing the calculation results with experiments performed on the designed PTGS prototype. A comprehensive evaluation approach was also proposed to support the comparative analysis of the arc dynamic behaviour and estimate the arc‐controlling capability of the designed electrode to further assess the dynamic performance of the designed PTGS. This approach could quantitatively estimate the arc behaviour from a spatial scale, the variation of characterised parameters such as temperature associated with arc behaviour is concerned as well, which reasonably supports the electrode optimum design and the PTGS. Abstract : Following the design demands of the protective switch used in ±800 kV hybrid UHVDC system, a plasma‐triggered‐based protective gas switch (PTGS) is developed with performing the comparative study of its dynamic performance by considering the arc dynamic behaviour induced by the transverse magnetic field (TMF)‐based electrode used in the PTGS.A 3‐dimensional (3D) magnetohydrodynamic model (MHD) was established to computationally evaluate the effects of electrode structure variation on arc rotation characteristics. A comprehensive evaluation approach was also proposed to support the comparative analysis of the arc dynamic behaviour and estimate the arc controlling capability of the designed electrode to further assess the dynamic performance of the designed PTGS.